Bohns' nodules: A lesser reported clinical entity - Rahul Kaul; Atul Bali; Vijay Lal; Rishu Koul (Wolters Kluwer Medknow Publications, 2022)
Bohns' nodules is a transient oral mucosal condition found mainly in Caucasian infants which are usually asymptomatic and do not interfere with feeding. This is a case report of a 4-month-old female was brought by her mother to a dental clinic with the chief complaint of swelling present on the gum of the upper jaw. The parents of the child were counseled and reassured and no treatment of any kind was performed.